Growth and investigation of epitaxial semiconductor films - Cullis, A (1972)
The work described in this thesis is concerned with the growth and examination of thin Si and Ge films. These were deposited by sublimation and evaporation techniques in UHV, using apparatus constructed by the author, The source of deposited material was heated by electron bombardment, while the substrates were heated either directly by the passage of an electric current or indirectly upon a Si bar, depending upon their electrical conductivity. The various substrates used were Si and the insulators sapphire, diamond and β-SiC. The grown films were studied by use of the optical microscope, the transmission electron microscope and the scanning electron microscope. The main object of the work was to investigate the structural perfection of these films, to deduce information concerning their growth mechanisms and to compare the observations with suitable theoretical models. The initial growth of Si films on unpreheated (111) Si substrates, held at temperatures around 900°C, was deduced to have been by nucleation (after an initial induction period), since irregular Si growth centres were produced. These eventually overlapped to give a channelled film containing few crystallographic defects. The dependence of the number density of Si growth centres upon deposition conditions was correlated with different theoretical relationships derived separately by Joyce et al (1967) and Logan (1969). It was deduced that the smallest stable nuclei contained 3 Si atoms, and that the activation energy for surface diffusion of Si was ~0.55 eV (Joyce et al) or ~1.1 eV (Logan). These observations and deductions were compared with analogous results obtained by Joyce et al, who grew Si films by silane pyrolysis. All the results were discussed in relation to initial growth processes, and various suggestions were put forward to account for certain unexpected features. Possible impurity effects were considered in detail and related to observed film growth characteristics. When (111) Si substrates were cleaned using heat treatment at 1250°C in UHV surface steps were generated, and these moved across the substrates in a [1̅1̅2] type direction. When Si deposition was initiated the direction of step motion reversed as growth took place. The steps were pinned in many places by impurity particles, which caused the production of deep pits in the grown films. Transmission electron energy loss analysis showed that the particles were SiC. The dependence of the Si film growth upon deposition conditions, the state of the substrate surface and the presence of contaminating gases was also investigated. The nature of both sublimation and growth step motion across substrate surfaces was analysed using theoretical models, and this showed that in the absence of pinning effects, the motion was generally that expected for a clean surface. Ge films were deposited on to (111) Si substrates at temperatures around 800°C. The thinnest films were composed of growth centres which were mostly triangular in shape, and this showed that initial growth had been by nucleation. A tentative comparison of experimental data with theoretical models indicated that the smallest stable Ge nucleus may have been composed of 4 atoms. TEM examination of the Ge films showed that they grew with the same crystallographic orientation as their Si substrates. However, the films contained many crystallographic defects, and some of the most prominent were continuous networks of misfit dislocations, which occurred over each entire Ge/Si interface. The spacings of the dislocations in such networks were non-ideal, and this was taken to indicate that considerable Ge/Si alloy formation had taken place. Deposition of Si on to heated (0001) sapphire substrates gave films which grew by initial nucleation with the epitaxial relationships (111)Si//(0001)Al2O3 and [11̅0]Si//[112̅0]Al2O3. The thinnest films were composed of equal proportions of two 60° rotational twins, and often contained large numbers of planar defects. However, films a substantial fraction of a micron in thickness contained misorientations of a more general nature, and with increasing thickness ultimately became polycrystalline. High resolution TEM studies provided no evidence of an interfacial misfit dislocation network, but instead indicated that a chemical reaction had taken place between the Si and the sapphire during deposition. Si films were also grown upon both (111) diamond and (111) βSiC substrates, and once again initial growth was by nucleation. Thicker films on diamond substrates exhibited significant orientation retention despite the very large crystallographic mismatch. Work was also carried out involving the high resolution TEM studies of closely spaced misfit edge dislocation networks at the Ge/(111)Si interface. It was generally possible to obtain either fringe or structural images depending upon the nature of the diffraction conditions, and this behaviour was examined in detail and discussed with special reference to the work of Thölén (1970). Use of the weak-beam technique (Cockayne et al, 1969) enabled the network structures to be investigated in detail. While it was observed that all the intrinsic dislocation nodes had a relatively uniform extension, the extrinsic nodes had mostly a much smaller extension and approximately half appeared to be completely contracted. Also, using 111̅ type Bragg reflections, the intensity of the TEM contrast exhibited by the different kinds of node stacking fault were markedly dissimilar, and depended upon the sense of the deviation from the exact Bragg position. These studies were extended to observations of dislocation networks produced by deformation in single crystal Si. Measurements of the dimensions of intrinsic nodes, which were all extended, yielded values for the intrinsic stacking fault energy in Si of ~58 or ~71 ergs cm-2, depending upon the type of measurement employed. Only half the extrinsic nodes were extended, and this behaviour was interpreted in terms of an energy barrier to node extension. Using 111̅ type reflections, the node contrast behaviour was analogous to that observed in the Ge/(111)Si system. This was correlated with the contrast behaviour of inclined stacking faults, and the image intensity appeared to depend upon the sign of (g.R)s. Using 224̅ type reflections, dissociated dislocation contrast was interpreted in terms of interactions between the strain fields of the bounding partial dislocations. In conclusion, suggestions were put forward concerning possible extensions of the present work, and these involved both film growth studies and investigations of TEM contrast behaviour.